Transformation of the value and sense sphere of the cadets from higher education institutions with specific study conditions for police training - S. V. Kharchenko; A. O. Siroshtan (Bulletin of Kharkiv National University of Internal Affairs)
The importance of personal value orientations for determining the motives of behaviour has been demonstrated. The changes in the polystructural value orientations of the cadets from higher education institutions with specific study conditions for police training under the influence of quarantine measures and martial law have been studied. The study was carried out on the basis of Kharkiv National University of Internal Affairs. The methodology of polystructural value orientations of personality by S. Bubnov and the U-criterion of Mann-Whitney were used in the study.